Burnout, anxiety and depression risk in medical doctors working in KwaZulu-Natal Province, South Africa: Evidence from a multi-site study of resource-constrained government hospitals in a generalised HIV epidemic setting - Thejini Naidoo; Andrew Tomita; Saeeda Paruk (2020)
Globally, burnout in medical doctors (MDs) is concerning, with higher rates reported in studies conducted in South Africa (SA). This psychological syndrome leads to serious health consequences, and jeopardises patient care. Despite this, there is no data pertaining to these potential adverse mental health outcomes in KwaZulu-Natal (KZN) Province, SA, where it is overshadowed by the fight against priorities such as HIV and AIDS/TB. This study therefore aimed to establish the nature and extent of burnout, anxiety and depressive symptoms and their associations among public sector MDs in KZN. A cross sectional study was conducted among MDs at five KZN public sector training hospitals to investigate their associations with practitioner (individual) and organisational factors using the Maslach Burnout Inventory–Human Services Survey (MBI-HSS), the Generalised Anxiety Disorder-7 (GAD-7) questionnaire and the Patient Health Questionnaire-9 (PHQ-9). Of the 150 participants, 88 (59.0%) screened positive for burnout, as indicated by high scores on the emotional exhaustion or depersonalisation subscales in the MBI-HSS. One fifth screened positive for anxiety (n = 30) and depressive symptoms (n = 32). Burnout was significantly associated with individual factors of anxiety (p<0.01) and depressive (p<0.01) symptoms based on adjusted logistic regression models. Organisational factors, such as lack of clinical supervisor support (p<0.01) and hospital resources (p<0.01), were significantly associated with burnout based on the bivariate analyses. Burnout, anxiety and depressive symptoms in MDs are highly prevalent and intertwined in resource constrained KZN public training hospitals. Addressing burnout at individual and organisational levels is important to mitigate its adverse effects.